Hearing colors: an example of brain plasticity - Alfaro, Arantxa; Bernabeu, Ángela; Agulló, Carlos; Parra, Jaime; Fernández, Eduardo (Frontiers in Systems Neuroscience, 2015)
Sensory substitution devices are providing new ways for improving or replacing sensory abilities that have been lost due to disease or injury, and at the same time offer unprecedented opportunities to address how the nervous system could lead to an augmentation of its capacities. In this work we have evaluated a color-blind subject using a new visual-to-auditory sensory substitution device (SSD) device called “Eyeborg”, that allows colors to be perceived as sounds. We used a combination of neuroimaging techniques including Functional Magnetic Resonance Imaging (fMRI), Diffusion Tensor Imaging (DTI) and proton Magnetic Resonance Spectroscopy (1H-MRS) to study potential brain plasticity in this subject. Our results suggest that after 8 years of continuous use of this device there could be significant adaptive and compensatory changes within the brain. In particular, we found changes in functional neural patterns, structural connectivity and cortical topography at the visual and auditive cortex of the Eyeborg user in comparison with a control population. Although at the moment we cannot claim that the continuous use of the Eyeborg is the only reason for these findings, our results may shed further light on potential brain changes associated with the use of other SSDs. This could help to better understand how the brain adapts to several pathologies and uncover adaptive resources such as cross-modal representations. We expect that the precise understanding of these changes will have clear implications for rehabilitative training, device development and for more efficient programs for people with disabilities.